Sistema operacional e biblioteca de funções para plataformas MPSOC: um estudo de caso para simuladores de reservatórios - Oliveira, Tadeu Ferreira (2010)
The increasingly request for processing power during last years has pushed integrated circuit industry to look for ways of providing even more processing power with less heat dissipation, power consumption, and chip area. This goal has been achieved increasing the circuit clock, but since there are physical limits of this approach a new solution emerged as the multiprocessor system on chip (MPSoC). This approach demands new tools and basic software infrastructure to take advantage of the inherent parallelism of these architectures. The oil exploration industry has one of its firsts activities the project decision on exploring oil fields, those decisions are aided by reservoir simulations demanding high processing power, the MPSoC may offer greater performance if its parallelism can be well used. This work presents a proposal of a micro-kernel operating system and auxiliary libraries aimed to the STORM MPSoC platform analyzing its influence on the problem of reservoir simulation